1999
DOI: 10.1055/s-1999-2721
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Electron Deficient Alkenes Using tert-Butyl Hydroperoxide and 1,5,7-Triazabicyclo[4.4.0]dec-5-ene and its Derivatives

Abstract: Epoxidation of Electron Deficient Alkenes Using tert-Butyl Hydroperoxide and 1,5,7-Triazabicyclo[4.4.0]dec-5-ene and Its Derivatives. -Sensitive epoxyquinones are efficiently prepared by enone epoxidation using cyclic guanidines (I) as promoters. Enantiopure guanidine derivatives show promising results in asymmetric epoxidation reactions. The investigation is presented in connection with syntheses of epoxyquinone antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…To circumvent this issue,w ed ecided to transform the quinone acetal 25 into epoxy ketone 28,inthe hope that this compound would show improved chemical stability (Scheme 11). Indeed, nucleophilic epoxidation of 25 [25] gave…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To circumvent this issue,w ed ecided to transform the quinone acetal 25 into epoxy ketone 28,inthe hope that this compound would show improved chemical stability (Scheme 11). Indeed, nucleophilic epoxidation of 25 [25] gave…”
Section: Angewandte Chemiementioning
confidence: 99%
“…More recent innovations in this regard include the use of basic hydrogen peroxide in an ionic liquid/aqueous biphasic system [484] or aqueous hydrogen peroxide in the presence of natural phosphate [485] or hydrotalcite with ultrasound [486]. Non-aqueous systems commonly employ TBHP, and this oxidant can be effectively catalyzed by a non-nucleophilic base, such as the guanidine derivative 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) [487], or even by potassium fluoride adsorbed onto alumina [488]. The methodology is not limited to conventional nucleophilic chemistry: electron-deficient alkenes can also be epoxidized under electrochemical conditions using a silver(III)oxo bis(2,2 0 -bipyridine) catalyst [489] as well as with more electrophilic oxidizing agents, such as iodosylbenzene [490].…”
Section: Epoxidation Of Electron-deficient Alkenesmentioning
confidence: 99%
“…Genki et al reported the epoxidation reaction of dienone using a combination of tertbutyl-hydroperoxide and a guanidine base [56]. Applying this methodology, they achieved a synthesis of (AE)-preussomerin L (188) [56].…”
Section: Heteroatom Conjugate Additionmentioning
confidence: 99%